A Model of Queer STEM Identity in the Workplace. Issue 13 (9th November 2020) - Mattheis, Allison; De Arellano, Daniel Cruz-Ramírez; Yoder, Jeremy B.
ABSTRACT: Science, technology, engineering, and mathematics (STEM) fields are often stereotyped as spaces in which personal identity is subsumed in the pursuit of a single-minded focus on objective scientific truths, and correspondingly rigid expectations of gender and sexuality are widespread. This paper describes findings from a grounded theory inquiry of how queer individuals working in STEM fields develop and navigate personal and professional identities. Through our analysis, we identified three distinct but related processes of Defining a queer gender and/or sexual identity, Forming an identity as a STEM professional, and Navigating identities at work. We found that heteronormative assumptions frequently silence conversations about gender and sexuality in STEM workplaces and result in complicated negotiations of self for queer professionals. This analysis of the personal accounts of queer students, faculty, and staff in STEM reveals unique processes of identity negotiation and elucidates how different social positioning creates challenges and opportunities for inclusivity.